2018
DOI: 10.1111/liv.13860
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is associated with decreased lung function

Abstract: Nonalcoholic fatty liver disease was associated with decreased lung function at baseline but was not associated with accelerated lung function decline in the propensity score-matched cohort. However, hepatic fibrosis was significantly associated with rapid forced vital capacity decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
(84 reference statements)
0
26
0
1
Order By: Relevance
“…[2] Patients with metabolic associated fatty liver disease (MAFLD), [3] formerly known as non-alcoholic fatty liver disease, are often obese and have additional metabolic risk factors which may translate to a greater risk from respiratory diseases. [4][5][6][7] It is currently not known whether MALFD patients are also more likely to have greater COVID-19 severity of illness. This study investigated the association between MAFLD and COVID-19 severity.…”
mentioning
confidence: 99%
“…[2] Patients with metabolic associated fatty liver disease (MAFLD), [3] formerly known as non-alcoholic fatty liver disease, are often obese and have additional metabolic risk factors which may translate to a greater risk from respiratory diseases. [4][5][6][7] It is currently not known whether MALFD patients are also more likely to have greater COVID-19 severity of illness. This study investigated the association between MAFLD and COVID-19 severity.…”
mentioning
confidence: 99%
“…The motivating example for this research is a NAFLD study including observational longitudinal data meant to examine the association between NAFLD and lung function in the general Korean population (Lee et al, 2018). The main question of interest in this study was: is there any difference in subjects' lung function and body mass index (BMI) between the NAFLD and non-NAFLD groups?…”
Section: Motivating Examplementioning
confidence: 99%
“…Of the total 20 112 subjects who underwent routine health screening examinations including hepatic ultrasonography and pulmonary function tests, 11 892 were randomly selected as being in the NAFLD and non-NAFLD groups, with the propensity score matched to the non-NAFLD group (1:1 ratio). NAFLD was defined as the presence of fatty liver, as determined by ultrasonography, with none of the following other possible causes of chronic liver disease: (a) significant alcohol consumption, (b) positivity for hepatitis B surface antigen or antibodies against the hepatitis C virus, and (c) other known etiologies of chronic liver disease (Lee et al, 2018). In order to measure chronic obstructive pulmonary disease, forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) were measured at each visit.…”
Section: Motivating Examplementioning
confidence: 99%
“…Moreover, several studies reported a significant association between NAFLD and decreased lung function in the general population. [3][4][5][6][7] However, detailed underlying mechanisms still remain unresolved.…”
Section: Introductionmentioning
confidence: 99%